(untitled) (Journal of Hama University, 2026)
This Research Aimed To Identify The Availability Of Basic Science Processes Skills In Kindergarten Booklet Third Category And Its Guide, And In Order TO Achieve The Research Aims The Researcher Adopted The Content Analysis Method, One Of The Methods Of The Descriptive Approach, Where It Prepared A List Of Basic Science Processes Skills That Formed In Its Final Form Of (8) Main Skills And (33) Sub-Skills, Then The Same List Was Approved In Preparing The Booklet Analysis Form And Its Guide, Check Her Sincerity And Stability. The Results Of The Research Showed That Basic Science Processes Skills Were Available In The Booklet And Its Guide, But In Varying Proportions As Follow: Communication Skill Came In First Ranking, With Repetition (1414), And A Percentage (51.10%), Followed By Observation Skill With Repetition (550), And A Percentage (19.88%), Then Classification Skill With Repetition (350), And A Percentage (12.65%), Then Using Numbers Skill With Repetition (233), And A Percentage (8.42%), Then Using Time And Place Relationships Skill With Repetition (107), And A Percentage (3.87%), Then Reasoning Skill With Repetition (101), And A Percentage (3.65%), Then Measurement Skill With Repetition (7), And A Percentage (0.25%), And Prediction Skill Came In Last Ranking With Repetition (5), And A Percentage (0.18%).